Toxicity of Solanum surattense against freshwater host snail Indoplanorbis exustus - Kumar, Pradeep (International Journal of Scientific Research in Biological Sciences, 2021)
Fascioliasis is a serious parasitic zoonotic disease caused by Fasciola. The carrier of Fasciola is a freshwater host snail Indoplanorbis exustus. The population of snail control is may be an effective technique for the control of fascioliasis infections. Synthetic molluscicides are effective for control of snail population but their cause’s adverse effect on non-target organisms and aquatic environment. Some plant families are potent sources of molluscicides. The present studies were designed for the evaluation of the molluscicidal efficacy of the medicinal plant Solanum surattense against snail I. exustus. Toxicity experiment of dried leaf powder of S. surattense and their organic extracts (ether, chloroform, methanol, acetone, and ethanol) and column purified was exposed against I. exustus and observed up to 96 hours (96h) at different concentrations of the treatments. Toxicity against I. exustus was noted at 24h interval up to 96h exposure and calculates lethal values and different parameters. Lethal Concentrations (LC50) of leaf powder of S. surattense were 24h exposure 185.26mg/l and at 96h 180.30 mg/l. The ethanolic extracts of dried leaf powder of S. surattense were more toxic against I. exustus among all the extracts. The present study shows that the S. surattense is a potent source of molluscicides and their different preparations revealed the new approaches that how the active components of this plant perform mode of action in the snail body.